Solubility and Dissolution Rate Enhancement of Poorly Soluble Telmisartan using Hydrotropy Method - Shah, Nirmal (Asian Journal of Pharmaceutics (AJP), 2024)
Objectives: Drugs given by oral route will undergo dissolution followed by permeation then it reaches to blood. Low water solubility is the foremost issue that comes upon with the development of dosage forms for newly discovered drugs as well as old drugs. Telmisartan is a class II category drug under the biopharmaceutical classification system, which limits its bioavailability to about 40%. Hydrotropy method has several advantages compared to other methods such as cost-effectiveness, ease of process, compatibility, scalable, and flexibility to varieties of dosage forms. Henceforth, an attempt has been made to improve the solubility of telmisartan using the hydrotropy method. Materials and Methods: Three different hydrotropic agents (urea, mannitol, and lactose) in different concentrations (10–50%) were used to find the solubility of the drug. The design of an expert statistical tool was utilized to optimize the best concentration of hydrotropic agent for having maximum solubility of the drug. Results: In a 40% urea blend, the solubility was obtained approximately 25.87 times more than pure drug (0.003 mg/mL) which showed the potential of the hydrotropic agent. This obtained optimized batch was further characterized for drug release profile and other related parameters. The optimized concentration of urea showed 87.46 ± 0.17% of drug release in 8 h which is relatively higher than the plain drug release. Conclusion: Therefore, it can be concluded that the 40% concentration of urea as a hydrotropic agent showed to be a key factor for enhancement of solubility followed by dissolution of poorly soluble telmisartan drug.